Fictionalizing Anthropology : Encounters and Fabulations at the Edges of the Human - McLean, Stuart (Stuart John) (Book collections on Project MUSE., 2017)
What might become of anthropology if it were to suspend its sometime claims to be a social science? What if it were to turn instead to exploring its affinities with art and literature as a mode of engaged creative practice carried forward in a world heterogeneously composed of humans and other than humans? Stuart McLean claims that anthropology stands to learn most from art and literature not as evidenceto support explanations based on an appeal to social context or history but as modes of engagement with the materiality of expressive media-including language-that always retain the capacity to disrupt or exceed the human projects enacted through them. At once comparative in scope and ethnographically informed, Fictionalizing Anthropology draws on an eclectic range of sources, including ancient Mesopotamian myth, Norse saga literature, Hesiod, Lucretius, Joyce, Artaud, and Lispector, as well as film, multimedia, and performance art, along with the concept of fabulation(the making of fictions capable of intervening in and transforming reality) developed in the writings of Bergson and Deleuze. Sharing with proponents of anthropologys recent ontological turn, McLean insists that experiments with language and form are a performative means of exploring alternative possibilities of collective existence, new ways of being human and other than human, and that such experiments must therefore be indispensable to anthropologys engagement with the contemporary world.